The Assignment and Division of the Tax Base in a System of Hierarchical Governments - William H. Hoyt (Center for Economic Studies and ifo Institute (CESifo), 2016)
Vertical externalities, changes in one level of government's policies that affect the budget of another level of government, may lead to non-optimal government policies. These externalities are associated with tax bases that are shared or “co-occupied” by two levels of government. Here I consider whether the co-occupancy of tax bases is desirable. I examine the optimal extent of the tax bases of a lower level of government (local) and a higher level (state). I find that it is optimal to have co-occupancy in the absence of other corrective policies if commodities in tax base are substitutes. Further, if the state government can differentially tax the co-occupied segment of the tax base and the segment it alone taxes it will obtain the (second-best) outcome obtained with other policy instruments such as intergovernmental grants. Finally, if there are horizontal externalities generated by cross-border shopping, there is still reason to co-occupy the tax base if commodities are substitutes. As well, local governments should have those commodities with the lowest cross-border shopping costs in their tax base.
Keywords: H20; H71; H73; R12; R28; R41; 330; fiscal competition; vertical externalities; tax base co-occupancy